Selective RAR agonists for acne vulgaris: A narrative review. (26th February 2020) - Kassir, Martin; Karagaiah, Priyanka; Sonthalia, Sidharth; Katsambas, Andreas; Galadari, Hassan; Gupta, Mrinal; Lotti, Torello; Wollina, Uwe; Abdelmaksoud, Ayman; Grabbe, Stephan; Goldust, Mohamad
Abstract: Background: Acne vulgaris is a chronic disfiguring inflammatory disease of adolescents and adults affecting up to 90% of the population around the world. The sequence of etiopathogenesis in acne is not completely understood but involves abnormalities in sebum production, follicular plugging, proliferation of propionibacterium acnes, and chronic inflammation. Aims: This review aims to summarize the features of the topical selective RAR agonists in treating acne vulgaris with a special emphasis on the 4th generation topical retinoid trifarotene. Methods: Studies were identified by searching electronic databases (MEDLINE and PubMed) till August 2019 and reference lists of respective articles. Only articles published in English language were included. Results: Topical retinoids have been first line of treatment for more than 30 years now in treating mild to moderate acne vulgaris. Third generation retinoids like adapalene and tazarotene are selective RAR and γ agonists, having an additional anti‐inflammatory action along with their comedolytic effects and work well in combinations with topical antibiotics, due to the stability of chemical composition. Conclusion: Trifarotene is a new 4th generation retinoid with selective action on RAR‐γ receptor alone, which is specific for skin, and it is safe for long‐term maintenance therapy with good efficacy and tolerability.